Analysis of factors affecting the sales of skincare products online by women in Pune - Agamya Dixit (International Journal of Advanced Science and Technology, 2020)
Indian skin care market has grown significantly in the past decade with an increase in awareness and purchasing power of women. A flawless complexion is now coveted by more women than ever before and this desire is backed by their purchasing ability. Resultantly, there has been an explosion of both Indian and foreign beauty brands in the market that are now offering an array of products for every skin care concern under the sun. This is also the era of technology and convenience. There has been an explosion of e-commerce platforms that lend choice, convenience and availability of products to the consumers. A large number of skin care companies have created an online presence in order to make sales online to this growing customer base that is buying skin care products from e-commerce platforms . This paper focuses on factor analysis of various attributes of skincare products as well as attributes of e-commerce platforms that influence sales of skin care products online in an attempt to understand which factors most strongly motivate women in Pune to buy skincare products on e-commerce platforms. This research was conducted by distribution of questionnaires that were filled by 100 respondents. The sample was comprised of women based in Pune who are regular consumers of skincare products. Data obtained is analyzed quantitatively using SPSS software. The study elucidated that certain factors like brand variety, discounts, convenience and provision of free samples positively affect consumer attitude towards purchasing skin care products online on e-commerce platforms.